Upregulation of Endothelin-1/Endothelin A Receptor Expression Correlates with Heparanase Expression in Ovarian Carcinoma - Nungki Anggorowati (Iranian Journal of Medical Sciences, 2018)
Background: Heparanase and endothelin-1/endothelin A receptor (ET-1/ETAR) expressions increase in cancer. This condition enhances tumor progression and correlates with poor survival. Limited data are documented regarding the role of heparanase and ET-1/ETAR in epithelial ovarian cancer (EOC). We sought to characterize the correlation between heparanase and ET-1/ETAR in EOC. Methods: Thirty patients with benign and malignant ovarian neoplasms were recruited in this study. Neoplasm subtypes were diagnosed by pathologists. RNA extraction was done in fresh frozen neoplasms while immunohistochemical (IHC) staining was done on ETAR, heparanase, and proliferation (Ki-67 antigen) in paraffin sections. Reverse transcriptase PCR was done to quantify the expression of preproET-1 (ppET-1), ETAR, and heparanase. ETAR and heparanase histoscores were done based on IHC staining. The Independent Samples t Test, ANOVA, and correlations were used for statistical analysis. Results: Heparanase and ETAR histoscores, ppET-1 and ETAR mRNA levels, and Ki-67 were significantly higher in the group with EOC than in the benign or borderline group, regardless of the histopathological types. The heparanase histoscore correlated with the ETAR histoscore (r=0.484, P=0.007) and the ETAR mRNA level (r=0.551, P=0.003). The level of ppET-1 mRNA correlated with both ETAR mRNA level and ETAR histoscore (r=0.603, P=0.001 and r=0.455, P=028, respectively). The ovarian neoplasms with high ppET-1 mRNA levels also tended to have high heparanase mRNA levels; however, the correlation was weak (r=0.354, P=0.07). Ki-67 correlated with the heparanase and ETAR histoscores (r=0.381, P=0.038 and r=0.477, P=0.008, respectively). Conclusion: Heparanase and ETAR were upregulated in EOC, and the correlation between heparanase and ETAR expressions was also elucidated in the current study.